Integrative Knowledge Management in Interdisciplinary Research Clusters - Jooß, Claudia; Thiele, Thomas; Vossen, René; Richert, Anja; Jeschke, Sabina (International Journal of Advanced Corporate Learning (iJAC), 2015)
Interdisciplinary Research (IDR) is described as a specific mode of collaboration: Besides the clash of different institutional cultures (e.g. different expectations/working processes), there is a clash of epistemic cultures (i.e. styles of thinking, different languages). Former research shows that the involved researchers demand an integrative knowledge management to support the expected integration of cultures. In this paper two major aspects regarding integrative knowledge management for IDR are discussed. On the one hand the need for integrative knowledge management based on the researchers’ perspective is depicted in the context of a use case. On the other hand the concept of a virtual mean is elaborated, which supports these needs. Both aspects underline the importance of a process-accompanying support in close coordination with the respective needs of the involved researchers.